Heterogeneous expectations among professional forecasters - Conrad, Christian; Lahiri, Kajal (Discussion paper, 2023)
Macroeconomic expectations of various economic agents are characterized by substantial cross-sectional heterogeneity. In this paper, we focus on expectations heterogeneity among professional forecasters. We first present stylized facts and discuss theoretical explanations for heterogeneous expectations. We then provide an overview of the empirical evidence supporting the different theories and point to directions for future research. Our literature review is complemented by empirical evidence based on the ZEW Financial Market Survey, covering the behavior of expectations heterogeneity during the recent surge in inflation in 2021 and 2022. A central finding is that differences in perceptions about the workings of the economy and heterogeneity in perceptions of the precision of new signals drive disagreement among professional forecasters. While the level of disagreement varies over the business cycle, differences in beliefs persist over time.